Islamic Elementary School Teachers’ Uncertainty on Distance Learning - Dewi, Nanda Rachma Kusuma; Palupi, Palupi (Universitas Muhammadiyah Surakarta, 2023)
Various obstacles were encountered by teachers during distance learning when covid-19 pandemi hit. Online teaching has become tough challenge for the forest edge villages’ school teachers in Madiun regency, Indonesia. Online teaching obstacles were also felt by the first-grade teachers at Madrasah Ibtidaiyyah Plus Al-Makmun (MI Plus Al-Makmun) which caused uncertainty. This study aims to examine the types of the teachers’ uncertainty and their uncertainty reduction strategies using uncertainty reduction theory. Descriptive qualitative method was used in this study and in-depth interview was conducted to gather data. The results of this study indicate that there are two types of uncertainty felt by the informants, the first is cognitive which is related to difficulties in understanding their students’ character and their insecurity about students’ understanding of school lessons, and the second is behavioral uncertainty which is related to how students respond and behave in learning process. Meanwhile, the teachers’ uncertainty reduction strategy are (1) passive strategies through secret observation, (2) active strategies by seeking information through parents and fellow teachers, and (3) interactive strategies by communicating directly with students